Heterogeneous catalytic direct amide bond formation - Nuria Martín; Francisco G. Cirujano (Catalysis Communications, 2022)
The synthesis of amides by the direct reaction of carboxylic acids with amines is an industrially relevant reaction in fine chemistry and drug synthesis, as well as a fundamental process for the construction of proteins in living organisms. To promote this process, the use of heterogeneous catalysts is preferred over their homogeneous counterparts, due to their advantages related to simple isolation, recovery and recycling. In addition, peptide bond formation over solid surfaces is interesting not only from the point of view of industrial organic synthesis but also from their implications in the understanding of prebiotic chemistry. For all this, we have highlighted some of the most relevant reported heterogeneous catalysts for the direct amide bond formation, focusing not only on the physicochemical properties of the solid catalyst –such as porosity and acidity- and its catalytic performance but also on the current understanding of the reaction mechanism. Different types of active sites incorporated at the surface (and bulk) of the solid are reviewed here: inorganic, organic and hybrid organic-inorganic. Besides the nature of the active sites, their interplay with the support in which they are embedded is thoroughly described, where surface area and pore size are key properties of the solid catalyst.